Detoxification and nutritional enhancement of soy meal via microbial bioprocessing - Chen, Liyan (Kansas State University, 2013)
Soy meal (SM) is the main protein source for monogastric animals. Anti-nutritional factors in SM limited its usage for young monogastric animals. Aspergillus was investigated to degrade these factors and to enhance its nutritional value via solid state fermentation. Galacto-oligosaccharides were totally degraded from the initial 9.48 mmol/100 g, and trypsin inhibitor decreased from 10.7 TIU/mg to a non-detectable level after 36 hr fermentation. Structural polysaccharides decreased by 59% (w/w) and the degree of hydrolysis of SM protein increased from 0.9% to 7% (w/w) through the 7 d fermentation. Fermentation also modified nutritional factors. Protein content increased from 50.47% (w/w) to 58.93% (w/w) after 36 hr fermentation. Amino acid profile was significantly enhanced. Two - stage temperature-induced fermentation protocol was developed to increase the degradation rate of phytic acid by A. oryzae (ATCC 9362) and by A. ficuum (ATCC 66876). The first stage maximized phytase production with fermentation parameters obtained by central composite design. The second stage achieved maximum enzymatic degradation with parameters obtained by studying the phytase temperature characteristics. While using A. oryzae, 57% of phytic acid in SM was degraded by the two stage protocol compared to 39% degradation from single stage fermentation. For A. ficuum, the two-stage temperature fermentation protocol achieved a 98% degradation level of phytic acid degradation compared with the single stage process. Two-stage temperature-induced co-fermentation of A. oryzae and A. ficuum was investigated to simultaneously degrade phytic acid and soy protein with high efficiency. Co-fermentation of A. oryzae and A. ficuum resulted in higher phytic acid degradation than A. oryzae fermentation and superior protein hydrolysis compared to A. ficuum fermentation. Sterilization distorted the results of fermentation effect on soy allergens and soy protein degradation. Virginiamycin is a kind of bacterisin. It was added to A. oryzae solid state fermentation, to exclude the necessity of SM sterilization. Nonsterile, solid state fermentation using A. oryzae and virginiamycin showed the complete degradation of α and α’ subunits of β-conglycinin and decreased immunoreactivity of soy protein. The modified SM after microbial bioprocessing created an innovative product with enhanced characteristics with potential wider applications for feed industry.
Keywords: Soy meal; Fermentation; Aspergillus oryzae; Aspergillus ficuum; Phytic acid; Animal feed; Agriculture, General (0473)